Cerebellar tDCS and pain modulation: a critical integrative and systematic review - Betancur, Daniel Fernando Arias; Tarragó, Maria da Graça Lopes; Oliveira, Maria Eduarda Louzada; Peres, Sara Machado; Torres, Iraci L. S.; Fregni, Felipe; Caumo, Wolnei (Frontiers in Neurology, 2025)
BackgroundCerebellar transcranial direct current stimulation (ctDCS) has emerged as a promising non-invasive neuromodulatory approach for managing pain. Early evidence suggests beneficial effects on pain perception in both healthy individuals and patients with chronic pain. However, the underlying mechanisms and clinical efficacy remain unclear. This systematic review aimed to synthesize the current evidence on cerebellar involvement in pain processing and to evaluate the potential of ctDCS as a therapeutic intervention.MethodsA systematic search was conducted in PubMed, Embase, and the Cochrane Library, following PRISMA guidelines. MeSH and Emtree descriptors related to “Cerebellum,” “Pain,” and “tDCS” were used to identify relevant studies published up to December 11, 2024. Eligible studies were randomized controlled trials (RCTs) that investigated the effects of ctDCS on pain. Risk of bias was assessed using the Cochrane Risk of Bias Tool version 2 (RoB 2).ResultsOf 819 records screened, five RCTs met the inclusion criteria. The primary methodological limitations included incomplete reporting of randomization procedures and inadequate blinding of outcome assessors. Two studies lacked key demographic and clinical details, while one showed a high risk of bias due to repeated same-day stimulation. Despite these issues, Across the included studies anodal ctDCS generally increased pain thresholds and enhanced endogenous pain inhibition, whereas cathodal ctDCS tended to reduce thresholds. Neurophysiological findings supported these behavioral results, with EEG data showing modulation of cortical activity related to pain processing.ConclusionPreliminary findings suggest that ctDCS may modulate nociceptive pathways and enhance pain inhibition. However, the small number of studies and methodological heterogeneity limit the generalizability of current results. Further high-quality RCTs are needed to optimize stimulation protocols, assess long-term effects, and establish clinical benefits. This review supports the cerebellum as a relevant and underexplored target for neuromodulatory pain interventions.